ZONE OF GEOTHERMAL PROSPECTS BASED ON FAULT FRACTURE DENSITY (FFD) METHOD IN SUMANI REGION, WEST SUMATERA - Sasilani, Resni; Haryanto, Agus Didit; Hutabarat, Johanes; Hermawan, Dudi; Widodo, Sri (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
The presence of geothermal manifestations in the form of hot springs is closely related to the presence of permeability zones in the Sumani geothermal system, West Sumatra. The permeable zone allows fluid circulation where meteoric water seeps to fill the reservoir and emerges on the earth's surface as a manifestation of hot springs. This study aimed to identify those permeable zones based on lineament density analysis using the Fault Fracture Density (FFD) method on ASTER GDEM satellite imagery. Lineaments in this case was assumed to be associated with fractures or faults in geothermal areas. The method was used to analyze the presence of lineament on topographic maps and to clarify all lineaments in the study area by adjusting the irradiation angle of 0°, 225°, 270°, and 315° at a constant altitude of 45°. From the FFD method, high lineament density values were found in the southwest of the study sites. The pattern of lineaments in the research area had northwest - southeast and southwest – northeast. The FFD analysis results were compiled with location of geothermal manifestations and geomorphological analysis which then showed positive results on the emergence of dominant hot springs depending on zones with high lineaments density and was located in the pyroclastic flow geomorphology unit with a difference in elevation between 500-1500 masl and slope of moderately steep to steep; indicating catchment area. Further research was needed to accurately understand about reservoir and the potential of geothermal reserves in the Sumani area.Keywords: Sumani Geothermal System, Fault Fracture Density, Geomorphological Analysis.